Persistence and change of Filipino family values the case of Barangay Coral, Mapandan, Pangasinan - Abad, Marjorie Samson; Paragas, Monica Mae De Guzman (2009)
As the society undergoes social changes, so does the institutions that comprise it. The family as one of those institutions where values are being transmitted; the basic institution where much of an individual's personality was develop. This research emphasizes the problem about the persistence and continuities of Filipino family values in Barangay Coral, Mapandan, Pangasinan. In line with this research are the following objectives: to be able to identify which of the family values had undergone changes and which are being practiced as they are; to be able to explain why values change and continue based on the data gathered during the conduct of the research; to be able to determine certain factors affecting the changes in Filipino family values; to be able to know the reason(s) behind the continuity of other values. These objectives provided the venue for increasing social awareness and interest regarding one of the most important institutions in the society - the Filipino family.Combinations of qualitative and quantitative methods were used to identify the existing values in Barangay Coral. Different instruments such as informal interview and survey were applied in gathering adequate data. To further explain the result, the analysis was framed with the use of Robin Williams' fourfold test on the values carrier -- Author's abstract.